Public-Private Partnerships (PPP) in the Philippines: Issues and Prospects - Jack B. Isolana (Recent Trends in Arts and Social Studies Vol. 9, 2023)
In the Philippines, Local Government Units (LGUs) are working to change the administration and functioning of public markets, and the study looked at how well these LGUs were internalizing the basic ideals of New Public administration (NPM). The study evaluated the effectiveness of PPP/BOT Public Markets in resolving the enduring issues with public markets in the Philippines using Public Private Partnership (PPP) as a framework of NPM for infrastructure development and service delivery. It questioned whether PPP had made public markets run more efficiently as a reform tool. Five of the nation’s first PPP public markets, including the Mandaluyong Public Market in Mandaluyong City, the Carmen and Cogon Public Markets in Cagayan de Oro City, the Suki Market in Quezon City, and the Bocaue Public Market in Bocaue, Bulacan, were reviewed to support the evaluation. As performance indicators, it looked at management and organization, the range of facilities and services, LGU revenue income and expenditures, vendor income from the market, and client satisfaction with the caliber of the facilities and services. Case studies, content analyses, ocular inspections, and interviews with city and municipal administrators, market administrators, market vendors, and officials of market vendors organizations were some of the combined research approaches used to gather the study’s data. The study shows that while PPP has improved the performance of public markets during the early years of operation, these gains and all advances were not sustained by the LGUs when management and operation of public markets were turned over to them from the private project proponent-operators. The study argued that to sustain public-private partnerships in the operation of the public market, it is imperative to institutionalize reforms in the structure, processes, mindsets of the leaders, and stakeholders. The institutionalization of NPM’s core values can be carried out effectively through localization of PPP as a policy so that the necessary legal and institutional frameworks for PPP will be anchored based on the need, strength, and weaknesses of the LGU concerned. The study makes a positive contribution to the on-going discourse on public sector reform in the Philippines particularly at the local level using PPP as a model. It enriches not only the literature of Public Administration but also provides valuable lessons in the praxis of governance.